From von Neumann architecture and Atanasoff’s ABC to Neuromorphic Computation and Kasabov’s NeuCube. Part II: Applications - Doborjeh, Maryam; Doborjeh, Zohreh; Gollahalli, Akshay Raj; Kumarasinghe, Kaushalya; Breen, Vivienne; Sengupta, Neelava; Ramos, Josafath Israel Espinosa; Hartono, Reggio; Capecci, Elisa; Kawano, Hideaki; Othman, Muhaini; Lei, Zhou; et al. (Springer International Publishing, 2018)
Spatio/Spector-Temporal Data (SSTD) analyzing is a challenging task, as temporal features may manifest complex interactions that may also change over time. Making use of suitable models that can capture the “hidden” interactions and interrelationship among multivariate data, is vital in SSTD investigation. This chapter describes a number of prominent applications built using the Kasabov’s NeuCube-based Spiking Neural Network (SNN) architecture for mapping, learning, visualization, classification/regression and better understanding and interpretation of SSTD.